Current Clubfoot Practices: POSNA Membership Survey - Oliver C. Sax; Larysa P. Hlukha; John E. Herzenberg; Philip K. McClure (MDPI AG, 2023)
Clubfoot management has advanced in the 21st century with increases in formal training, practitioner experience, and improved casting/bracing constructs. The Ponseti method is the gold standard, yet variations in application persist. This survey aims to identify current treatment practices among clubfoot practitioners within the Pediatric Orthopaedic Society of North America (POSNA). A 23-question online survey of members was conducted between June and August 2021. Eighty-nine respondents self-identified as clubfoot providers. Of these, 93.1% had an MD degree, 23.6% possessed >30 years' experience, and the majority (65.6%) worked in a teaching hospital associated with a medical school. Most responders (92.0%) were pediatric fellowship trained. A total of 51.7% had participated in a clubfoot training course. More than half (57.5%) noted changes to clubfoot management practices throughout their training. A majority used between four and seven (88.7%) long leg casts (98.4%), changed at seven-day intervals (93.4%). Plaster (69.4%) was most commonly used. The most common bracing device was Mitchell-Ponseti (72.9%). A mean 84.8% of clubfeet required tenotomy. The most common anesthetic agent was numbing gel (43.0%). Tenotomies mostly occurred in patients aged <6 months (63.1%). Tenotomy locations were operating room (46.5%), clinic (45.4%) and procedure room (8.1%). Cast removal was primarily performed with saws (54.7%). The mean incidence of observed cast burns was 5.5%. Most providers did not use a device to prevent cast burns (76.6%). Reported cast complications included slippage (85.9%), skin irritation (75.8%), and saw-related injuries (35.9%). Clubfoot management variations exist in orthotics, tenotomy indications and practices, and cast material. Casting complications continue to be a problem. Further studies are warranted to determine if certain practices predispose patients to specific complications.